Discriminating Disease Flare From Infection in Febrile Patients With Systemic Lupus Erythematosus in a Safety‐Net Hospital System: A Multicenter Study - Abhimanyu Amarnani; Flora Liu; Melissa Lee Wilson; Nathan Lim; William Stohl; Leanna Wise (ACR Open Rheumatology)
Objective The objective of this study was to assess clinical laboratory parameters that distinguish between disease flare and infection in febrile patients with systemic lupus erythematosus (SLE) at safety‐net hospitals in Los Angeles. Methods We reviewed electronic medical records of patients admitted from August 1, 2016, through July 31, 2019, categorizing them as disease flare, bacterial infection (culture positive), culture‐negative infection, and both flare and infection. Laboratory parameters collected within 48 hours of admission (complete blood cell count with differential, liver function panel, erythrocyte sedimentation rate [ESR], C‐reactive protein [CRP], C3, C4, lactate, procalcitonin, and ferritin) were analyzed. Results Several laboratory parameters significantly distinguished febrile patients with disease flare from those with infection. An optimized multivariable logistic regression model revealed that an elevated ESR:CRP ratio (>1.17), low white blood cell (WBC) count (<6.25 × 109/L), low absolute neutrophil count (<5.55 × 109/L), and low CRP (<113 mg/L), C3 (<44.5 mg/dL), and C4 (<13.5 mg/dL) levels helped discriminate disease flare from culture‐positive infection. These laboratory parameters yielded areas under the receiving operating characteristic curve of 0.87 (95% confidence interval [CI] 0.76–0.97) for flare versus culture‐positive infection and 0.94 (95% CI 0.88–1.00) for flare versus culture‐negative infection. These optimized models, using multiple laboratory parameters, significantly outperformed the ESR:CRP ratio alone (P < 0.02) in discriminating flare from infection. Conclusion The ESR:CRP ratio plus C3 and C4 levels, WBC count, neutrophil count, and monocyte count discriminate flare from either culture‐positive or culture‐negative infection in febrile patients with SLE. Our findings warrant prospective validation.